Structure–activity study of N-((trans)-4-(2-(7-cyano-3,4-dihydroisoquinolin-2(1H)-yl)ethyl)cyclohexyl)-1H-indole-2-carboxamide (SB269652), a bitopic ligand that acts as a negative allosteric modulator of the dopamine D2 receptor - Shonberg, Jeremy; Draper-Joyce, Christopher; Mistry, Shailesh N.; Christopoulos, Arthur; Scammells, Peter J.; Lane, J. Robert; Capuano, Ben (American Chemical Society, 2015)
We recently demonstrated that SB269652 (1) engages one protomer of a dopamine D2 receptor (D2R) dimer in a bitopic mode to allosterically inhibit the binding of dopamine at the other protomer. Herein, we investigate structural deter- minants for allostery, focusing on modifications to three moieties within 1. We find that orthosteric “head” groups with small 7-substituents were important to maintain the limited negative cooperativity of analogues of 1, and replacement of the tetrahydroisoquinoline head group with other D2R “privileged structures” generated orthosteric antagonists. Additionally, replacement of the cyclohexylene linker with polymethylene chains conferred linker length dependency in allosteric pharma- cology. We validated the importance of the indolic NH as a hydrogen bond donor moiety for maintaining allostery. Replacement of the indole ring with azaindole conferred a 30-fold increase in affinity while maintaining negative cooperativity. Combined, these results provide novel SAR insight for bitopic ligands that act as negative allosteric modulators of the D2R.